Amyloid-β reduces the expression of neuronal FAIM-L, thereby shifting the inflammatory response mediated by TNFα from neuronal protection to death. - Carriba, P.; Jimenez, S.; Navarro, V.; Moreno-González, Inés; Barneda-Zahonero, Bruna; Moubarak, R.S.; Lopez-Soriano, J.; Gutiérrez-Pérez, Antonia; Vitorica Ferrández, Javier; Comella, Joan Xavier (Cell Death & Disease, 2015)
The brains of patients with Alzheimer’s disease (AD) present elevated levels of tumor necrosis factor-α (TNFα), a cytokine that has a dual function in neuronal cells. On one hand, TNFα can activate neuronal apoptosis, and on the other hand, it can protect these cells against amyloid-β (Aβ) toxicity. Given the dual behavior of this molecule, there is some controversy regarding its contribution to the pathogenesis of AD. Here we examined the relevance of the long form of Fas apoptotic inhibitory molecule (FAIM) protein, FAIM-L, in regulating the dual function of TNFα. We detected that FAIM-L was reduced in the hippocampi of patients with AD. We also observed that the entorhinal and hippocampal cortex of a mouse model of AD (PS1M146LxAPP751sl) showed a reduction in this protein before the onset of neurodegeneration. Notably, cultured neurons treated with the cortical soluble fractions of these animals showed a decrease in endogenous FAIM-L, an effect that is mimicked by the treatment with Aβ-derived diffusible ligands (ADDLs). The reduction in the expression of FAIM-L is associated with the progression of the neurodegeneration by changing the inflammatory response mediated by TNFα in neurons. In this sense, we also demonstrate that the protection afforded by TNFα against Aβ toxicity ceases when endogenous FAIM-L is reduced by short hairpin RNA (shRNA) or by treatment with ADDLs. All together, these results support the notion that levels of FAIM-L contribute to determine the protective or deleterious effect of TNFα in neuronal cells.
Aβ reduces FAIM-L changing the neuronal response to TNFα
Keywords: Alzheimer, Enfermedad de; Citoquinas; Factor necrosante de los tumores; Alzheimer